Grounding Line Retreat and Ice Discharge Variability at Two Surging, Ice Shelf‐Forming Basins of Flade Isblink Ice Cap, Northern Greenland. Issue 2 (22nd February 2022) - Möller, Marco; Friedl, Peter; Palmer, Steven J.; Marzeion, Ben
Abstract: Ice discharge from Flade Isblink ice cap (NE Greenland) maintains an ice shelf at the northwestern fringe of the ice cap. The two outlet basins feeding this ice shelf surged during the late 1990s. Ice shelves are rare in Greenland and surges of ice shelf terminating glaciers even rarer. Understanding and explaining the evolution of ice mass changes in the two basins is hampered by a lack of knowledge about processes at their grounding zones. We determined, for the first time, the grounding line locations of these basins and analyzed their variability with time. We further quantified ice discharge and its variability during the period 1988–2020. We found that the grounding lines advanced slightly between 1993 and 1999 during the glacier surges, but showed overall retreats of 2.2 ± 1.3 km in basin 2 and 2.7 ± 0.9 km in basin 3 until 2019 over retrograde sloping beds. The retreats were promoted by increasing buoyancy forces due to increasing water depth, but opposing buttressing forces of the ice shelf induced a differing response of the grounding line in the two basins. Based on the observed patterns of flow and retreat, we characterized the surges as "Svalbard‐type", modified by buttressing effects of the ice shelf. We calculated total ice discharges over the study period of 1.85 ± 1.59 Gt in basin 2 and 1.38 ± 1.22 Gt in basin 3. We observed reductions in ice discharge of at least 90% after the surges, that persisted for the remainder of the period studied. Plain Language Summary: The ice cap Flade Isblink (NE Greenland) exhibits a floating ice shelf in front of its northwestern fringe. The two outlet glacier basins which feed this ice shelf experienced surges in the late 1990s. Comparable events have been very rare in Greenland. Little is known about the area where the grounded ice of the two basins of Flade Isblink becomes floating. This hampers an understanding of their ice mass changes. We mapped the grounding lines, that is, the lines where the ice becomes floating, of the two basins at different dates in order to study their variability with time. They advanced slightly together with the surges and afterward retreated by more than 2 km. We also calculated the amount of glacier ice that flowed out of the two basins into the ice shelf over the period 1988–2020: basin 2 lost an ice mass of 1.85 ± 1.59 Gt and basin 3 an ice mass of 1.38 ± 1.22 Gt. After the surges, the ice mass loss per year was at least 90% smaller than during the surges. From our analyses, we concluded that the surges should be characterized as modified "Svalbard‐type". Key Points: After slight advances in the 1996–2001 surges, the grounding lines of basins 2 and 3 retreated 2.2 ± 1.3 km and 2.7 ± 0.9 km until 2019 Surges of basins 2 and 3 were of "Svalbard‐type" whose characteristics were modified by buttressing effects of the downstream ice shelf Persistent slowdowns of ice discharge occurred in basins 2 and 3 after the surges, with discharge volumes decreasing by 90% and 96%